The University and Community Engagement: Recent Approaches - Mattson, Craig E. (Christian scholar's review, 2024)
Place-Based Community Engagement in Higher Education: A Strategy to Transform Universities and Communities Erica K. Yamamura and Kent Koth Published by Routledge in 2018 176pp / $44.95 / 9781620366776 Amazon Goodreads College as a Public Good: Making the Case through Community Engagement Karin Fischer Published by Chronicle of Higher Education in 2023 64 pp /...